(untitled) (Estudio Agustiniano, 2017)
An interpretative exercise is presented to present the novel poet Isidro Andrés Casado, inscribing him in the Greco-Latin, Christian-Augustinian and Hispanic-Leonese traditions as far as the conception of love and of the word is concerned. These, in turn, meet and dialogue with the verb and spirit of a poet who is open to modern aesthetics, contemporary reasons and feelings. It consists of four parts: 1. biographical review of the poet; 2. approach to his aesthetic-existential conception of love; 3. tasting a poetic that explains the form of the text and 4. outline a list of topics to dialogue about love with six great poets.